Feasibility study for the establishment of factory production of concrete blocks - Alaa Farhan Talib; zohair hassan abdullah; abdulnaser salih hadi (Iraqi Journal for Administrative Sciences, 2025)
This research dealt with detailed studying of project construction of factory production of concrete blocks and presented by manufacturing of building blocks by depending on the Iraqi designs and specifications and local building materials. Due to rebuilding and building movement inter country especially in field of the construction building units that speed working and needing of local market for half manufacturing materials or completed manufacture, the state and government work to block this type of projects because the projects have been important in bring and absorb labors those break up of work in addition to exploit of local raw materials in manufacturing without need to import and arrange on this of loss in different coin that country in great need for it. This research aims to analyze of technical path to manufacture hollow concrete blocks and designed with dimensions (15 × 20 × 40 cm), with determine internal layout of location requirements of the factory , economical to calculate production costs, percentage of the profit project , recovery duration of project and net present value. Results appear the annual production costs are equal (919.081.785 dinars), the percentage of profit project is equal (48 %) and recovery duration of project equal (2.3 year) and net present value was positive. and emphasize to an importance construction of this project.